PENGARUH PENERAPAN AKUNTANSI PERTANGGUNGJAWABAN PADA EFEKTIVITAS PENGENDALIAN BIAYA HOTEL BINTANG LIMA - Pradnyani, Ni Made Sinta; Erawati, Ni Made Adi (E-Jurnal Akuntansi, 2015)
Responsibility accounting is a tool used for the collection and reporting of cost basis in accordance with its responsibility center so that in the event of deviation can be designated responsible party. The data collection method is questionnaire method and the analytic technique used is multiple linear regression analysis. Based on the hypothesis testing results show that there are significant accounting implementation consisting of variable elements of the organizational structure, responsibility center, budgets, and expense reporting system on the effectiveness of cost control either simultaneously or partially. Companies can divide departments within the company based on responsibility center, as well as perform the encoding cost according to the responsible party.
Keywords: Responsibility accounting, effectiveness of cost control, organizational structure, budget, expense reporting system